The Disposal of Archive in doing its Protection (Case Study at State Islamic University Syarif Hidayatullah Jakarta dan Centre of Archive Administration University Indonesia) - Lolytasari, Lolytasari (Record and Library Journal, 2015)
This research discusses about the implication of disposal and explains the existence of Institution of archive in University which has a function to protect the archive. The problem in this study is how is the application of the archive disposal in University Indonesia that has no retention schedule and has a retention schedule.The objective of this research is to identify the program application of archive disposal and to assess the disposal of Â archive which is done by the Centre of Archive Administration University Indonesia becoming model of archive in the State Islamic University Syarif Hidayatullah Jakarta. The method of the research is descriptive qualitative. The result of this research is that UIN Syarif Hidayatullah Jakarta did not have record retention schedule. So itâs difficult to destroy the archives. And archive still keep in the unit, without make appraisal.